Modos de regulação e formação de competências profissionais : uma reflexão sob a luz da teoria do agir organizacional - Castro, André Luís de (2010)
Although many are searching the area of sotware development, yet there are gaps in relation to organizational dimensions: the formation of skills in the workplace is one. The purpose of this research is to examine to what extent the modes of regulation (heteronomy, autonomy, discretionarity) promote constraints to programmers competencies in Maringá - PR software local productive cluster. The theoretical approach that underlies this research is the theory of the Organizational Act proposed by Bruno Maggi (2006). This theory provides a reflection that highlights the relationship between modes of regulation at work and competencies formation. To obtain the information necessary to understand the object of study, were used the quantitative approach, from which was made use of a survey with closed and open questions. The analysis included the statistical methods such as analysis of frequency distribution and mean, the creation of indexes, where the concepts of formation, and testing of association and dependence between variables related to the modes of regulation, levels of decision making, cooperation, coordination and constraints. In relation to the concepts of formation, index empirically confirmed that the different types are perceived. This means that the various issues related to the same design, do indeed represent a specific construct according to respondents. The data indicated tight constraints to skills training related to modes of regulation in their sample. Poor evidence perception of constraints and relationship between the modes of regulation can be explained by one of the principal personal means of development competencies: the exchange of experiences between coworkers, which does not require necessarily the company that promotes it. The predominance of the concept of formation the system and act as a process also contributed to an explanation, since this concept is related to identifying needs and developing competencies among the rofessionals themselves. Moreover, the results indicate some trends: decision making can be shared between managers and programmers; usually cooperation is spontaneous; and coordination can occur with the participation of all in some situations. Factors that may contribute to the findings in relation to the constraints.